Alternative railway tools and sustainability in RAMS: A review - M. A, Muhammed Nor; A. F., Yusop; M. N., Omar; N. A., Abdul Hamid; W. M., Wan Mohamed (Springer, 2022)
RAMS is a tool and methodology that combines reliability engineering, availability, maintainability, and safety in a way that is tailored to the system’s goals. A comprehensive view on RAMS’s components and theory behind the underlying mathematical model is not to be found in journal publication. This paper would also discuss several benefits and sustainability of RAMS. Life Cycle Cost (LCC) would also being introduce as a complementary discipline in term of costing that normally regarded parallel to RAMS. There are a series of methods that being utilized at every discipline of the RAMS component such as Fault Tree Analysis (FTA), Failure Mode Effect Critical Analysis (FMECA), Reliability Block Diagram and many more. Some commonly used methods would be highlighted in this paper. RAMS application and implementation will aid asset owners, contractors, and operators in efficiently procuring, developing, and operating their assets. However, further research and analysis is needed in the railway industry to build a viable framework for project and operation implementation using both tools.